2018
DOI: 10.1111/cyt.12529
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology and sonographic features of ectopic thymic tissue diagnosed in paediatric FNA biopsies

Abstract: Ectopic thymic tissue is rarely present as a neck mass or thyroid nodule on FNA biopsy. The ultrasound imaging findings reveal a well-defined fusiform lesion with punctate bright echoes that could be misinterpreted as papillary thyroid carcinoma. The aspirates show a small lymphoid population, immunophenotypically compatible with thymic T-cells, in addition to scattered epithelial cells. Therefore, knowledge of the typical ultrasonographic and cytopathological features can help make a definitive diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
5
24
0
Order By: Relevance
“…Limitations of the current study include lack of pathology results to confirm diagnosis of ECT, and the fact that some children did not have follow‐up after initial diagnosis. Previous studies have used biopsy or FNA testing to confirm the high correlation between characteristic ultrasound features and the diagnosis of ectopic thymic tissue . Because this correlation has been demonstrated in the literature, we do not routinely biopsy lesions exhibiting these features unless the child is symptomatic or the diagnosis unclear.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Limitations of the current study include lack of pathology results to confirm diagnosis of ECT, and the fact that some children did not have follow‐up after initial diagnosis. Previous studies have used biopsy or FNA testing to confirm the high correlation between characteristic ultrasound features and the diagnosis of ectopic thymic tissue . Because this correlation has been demonstrated in the literature, we do not routinely biopsy lesions exhibiting these features unless the child is symptomatic or the diagnosis unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Most children underwent ultrasound imaging alone. Ultrasound imaging may be a reasonable option for diagnosis and surveillance in many cases as long as providers proceed with FNA or biopsy if there is growth or concerning features . Ultrasound is particularly useful in children as it avoids the need for general anesthetic and prevents radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have confirmed that the presence of an intrathyroidal thymus through cytology or surgery due to the fear that children with suspicious thyroid lesions are misdiagnosed ( 4 5 12 13 15 16 21 22 ). However, a few studies on the ultrasound characteristics and the prevalence of intrathyroidal thymus were based on US images only, without cytological evaluation, and suggested that US could be used as a common diagnostic tool to identify a benign intrathyroidal thymus ( 11 13 17 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, because US has become more frequently used in children, the characteristic features of intrathyroidal thymic tissue used to distinguish it from thyroid nodules have been reported more often, and this intrathyroidal thymus is now more frequently found as a common variant ( 8 11 12 13 14 15 ). Until 2015, 59 cases of ectopic thymic tissue mimicking thyroid nodules or neoplasia detected on US had been published and more cases have been reported since ( 12 13 15 16 17 18 ). The US features of an intrathyroidal thymus are similar to those of a normal thymus.…”
Section: Introductionmentioning
confidence: 99%